2021
DOI: 10.3390/ma14061455
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Morphology of the Saddle-Shaped Bronze Chips Briquettes Produced in the Roller Press

Abstract: This paper presents the results of the investigations of the properties of saddle-shaped copper alloy chips briquettes produced in a roller press. The physical and mechanical properties of the investigated briquettes were examined on their external surfaces as well as on their cross-sections. The density, chemical composition, microstructure analysis obtained with a 3D and scanning microscope, surface roughness and hardness of the obtained briquettes were investigated. The research proved the differentiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…The average stress values are 36÷40 MPa, where the minimum value is determined for the circumferential speed of the rollers of 0.2 m/s ( Figure 12 ). These results align with the experiments presented in [ 53 , 54 ], which demonstrated higher pressures and greater density of saddle-shaped briquettes in their upper part.…”
Section: Research Results and Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The average stress values are 36÷40 MPa, where the minimum value is determined for the circumferential speed of the rollers of 0.2 m/s ( Figure 12 ). These results align with the experiments presented in [ 53 , 54 ], which demonstrated higher pressures and greater density of saddle-shaped briquettes in their upper part.…”
Section: Research Results and Analysissupporting
confidence: 92%
“… A general correlation between pressure distribution, porosity, and temperature distribution: ( a ) pressure distribution—DEM; ( b ) map of the porosity distribution on the copper briquette cross-section [ 53 ]; ( c ) the thermographic image of the briquette after briquetting [ 54 ]. …”
Section: Figurementioning
confidence: 99%
“…From the analysis of both distributions, it can be concluded that higher local briquette temperatures in a given place correspond to better local density. Therefore, in the case of saddle-shaped briquette in the upper part of the briquette, the stresses and strain are greater, and those in the lower part-smaller, which is also confirmed by the recent research presented in the paper [76].…”
Section: Discussionsupporting
confidence: 80%
“…The highest temperature is obtained in the upper middle part of the briquette. In this part of the briquette from the front side, one can therefore expect the greatest packing of the material, resulting from the greatest compacting pressure acting at this point [46]. These results coincide with the simulation tests carried out for briquetting of fine-grained materials using the discrete element method [50].…”
Section: Temperature Distribution On Briquette Surfacessupporting
confidence: 78%
“…During the production of a briquette in a roller briquetting press, the pressure exerted on its external surface is not uniform [44]. Depending on the place on the surface, it may have a variable value [45,46]. The resulting compacting pressure distribution depends not only on the material properties but also on the geometry of the compaction unit and the briquette volume.…”
Section: Introductionmentioning
confidence: 99%